More knowledge, more choices? How peer recognition of physicians’ knowledge sharing affect patients’ consultation in online health communities - Xu, Zhen; Liu, Xiaochen; Meng, Lingguang; Lyu, Xuanxuan (Frontiers in Public Health, 2024)
Background: The advent of telemedicine has revolutionized healthcare consultations, primarily due to the digital era and global health concerns. Online healthcare communities (OHCs) have emerged as platforms for physicians to share health-related articles, promoting digital public health awareness and knowledge dissemination. The continuous dissemination of health knowledge by physicians online is considered a crucial driving force in attracting patients to seek online consultations. Methods: Based on the elaboration likelihood model and the information overload theory, this study explores how persuasive messages from other patients' peer recognition, including knowledge popularity and attractiveness, affect patients' consultation decisions. Additionally, the study examines the three-way interaction between knowledge popularity, attractiveness, and quantity in shaping patient consultations. Using data collected from 2676 physicians on haodf.com, this study established an ordinary least squares (OLS) regression model with time and city fixed effects to test the hypothesis. Results: The results show that: (1) peer recognition (knowledge popularity and attractiveness) from other patients positively impacts patients’ consultation; (2) knowledge attractiveness positively moderate the relationship between knowledge popularity and patients’ consultation; (3) there is a three-way effect of knowledge popularity, knowledge attractiveness, and knowledge quantity on patients’ consultation. Conclusion: Our findings offer valuable guidance for platform design and healthcare practitioners, boosting patient-physician engagement in online healthcare communities.